(untitled) (aSSIST Business Review, 2026)
This study aims to propose strategies to provide practical employment opportunities and support the successful settlement of Korean youth seeking jobs in Japan. With Japan facing a labor shortage due to a declining population and aging society, policies to attract foreign talent are being implemented. Simultaneously, Korea’s high youth unemployment rate has led to increased interest in overseas employment, with Japan being a favorable option due to its geographical and cultural proximity and stable working environment. The research analyzed Japan’s labor market, demand for foreign labor, and trends in Korean youth employment through literature reviews, case studies, and expert interviews. Key findings highlight Japanese language proficiency (JLPT N2 or higher), cultural adaptability, and network utilization as critical success factors. Successful cases demonstrated strong language skills, understanding of business etiquette, and effective use of employment support programs like K-Move. Conversely, failures were linked to insufficient preparation, cultural challenges, and lack of local settlement support. The study recommends integrated Japanese language and cultural training, enhanced settlement support, and labor exchange models through government and private-sector collaboration.